الدراسة الكيميائية لمستخلصات بعض النباتات الطبية المستخدمة في الطب التقليدي لعالج ارتفاع ضغط الدم في منطقة واد سوف - بن علي, نجاح; نسيب, حليمة (Université of eloued جامعة الوادي, 2020)
This work aims to detect and extract some secondary metabolites common in extracts of some plants traditionally used in the treatment of high blood pressure (Hypertension) in the Oued Souf region. Through a questionnaire, four plants were selected for the study: Allium sativum 81.57%, Ocimum basilicum 61.2%, Nigella sativa 34.77%, and Olea europaea 7.2%. The chemical study showed that the Allium sativum, Ocimum basilicum , Nigella sativa ,and Olea europaea contain a number of secondary metabolites, represented by alkaloids, sterols and triterpenes, glycosides and Saponine, while we noticed the absence of flavonoids and tannins in both Allium sativum, Nigella sativa, and their presence at Ocimum basilicum and Olea europaea The yield of the phenolic extract was estimated at 35.54% as the highest yield for the Allium sativum, while olive leaves Olea europaea recorded the highest alkaline yield of 2%.
التنوع الحيوي و فيزيولوجيا النبات
Keywords: الثوم ، أوراق الزيتون ، ضغط الدم ، الحبة السوداء ، الريحان; High blood pressure - Secondary metabolites - Allium sativum - Ocimum basilicum - Nigella sativa L - Olea europaea